Keanekaragaman Tumbuhan pada Berbagai Tata Guna Lahan di Kawasan Kars Pegunungan Kendeng Desa Sukolilo, Pati (Plant Diversity in Different Lands Use in Karst Region Mountains Kendeng Sukolilo village, Pati) - Angga Yuda Saputra; Erry Wiryani; Jumari J (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
Karst region has typical characteristics of ecosystems of high lime content that required plants which lived in the region tolerant with the content of lime and drought. There are any land use at Sukolilo village, the differences in land use affect the diversity of plants. This study aims to determined the index of diversity and importance value index of plant , as well as the importance of vegetation indiced on various land uses in the region. The plot study determination was conducted by purposive random sampling method by recording the number of species, widespread basal area and canopy closure at the level of plant trees, shrubs and herbs, and analyzed the data that obtained from different land uses. The results as a whole there are 156 plant species in 55 families, in details, at tree level there are 60 species, 69 species of shrubs level and 34 species of herbaceous level. The highest species diversity index was found on the land around the springs (3.18). While the importance value index found on Jati tree (Tectona grandis) on forest land of Perhutani (186.50). The differences in diversity on a variety of land use are because of human influenced in the utilization and management of land. Keywords: Plant Biodiversity, Land Use, Karst Regions, Kendeng Mountains Sukolilo